Trait–environment relationships could alter the spatial and temporal characteristics of aquatic insect subsidies at the macrospatial scale. Issue 3 (2nd December 2020) - Kopp, Darin; Allen, Daniel
Abstract : Ecological flows across ecosystem boundaries are typically studied at spatial scales that limit our understanding of broad geographical patterns in ecosystem linkages. Aquatic insects that metamorphose into terrestrial adults are important resource subsidies for terrestrial ecosystems. Traits related to their development and dispersal should determine their availability to terrestrial consumers. Here, we synthesize geospatial, aquatic biomonitoring and biological traits data to quantify the relative importance of several environmental gradients on the potential spatial and temporal characteristics of aquatic insect subsidies across the contiguous United States. We found the trait composition of benthic macroinvertebrate communities varies among hydrologic regions and could affect how aquatic insects transport subsidies as adults. Further, several trait–environment relationships were underpinned by hydrology. Large bodied taxa that could disperse further from the stream were associated with hydrologically stable conditions. Alternatively, hydrologically variable conditions were associated with multivoltine taxa that could extend the duration of subsidies with periodic emergence events throughout the year. We also found that anthropogenic impacts decrease the frequency of individuals with adult flight but potentially extend the distance subsidies travel into the terrestrial ecosystem. Collectively, these results suggest that natural and anthropogenic gradients could affect aquatic insect subsidies by changing the trait composition of benthic macroinvertebrate communities. The conceptual framework and trait–environment relationships we present shows promise for understanding broad geographical patterns in linkages between ecosystems.